Ваlance of thyroid hormones in conditions of the growing normobaric hypoxia in persons with different degrees of adaptation to the loads of anaerobic character - А. V. Yashkov; V. A. Polyakov; M. V. Shelykhmanova; N. V. Sushina; E. Yu. Prosvirov (National Electronic Information Consortium (NEICON), 2020)
Objective: is to study the reaction of the pituitary-thyroid system in conditions of acutely increasing normobaric hypoxia in healthy individuals. Materials and methods: a dynamic study of the reaction of the pituitary-thyroid system under conditions of acutely increasing normobaric hypoxia in 24 healthy individuals with varying degrees of adaptation to physical activities of anaerobic nature was carried out. The study of changes in hormonal background was conducted by radioimmune method. In the training of 12 rowing athletes (average age 22±0.7 years) of the main group, anaerobic loads were widely used. The comparison group consisted of 12 conditionally healthy men (average age 21.5±0.6 years) who were not involved in sports Results: with the development of hypoxic state in individuals who train under anaerobic exercise conditions, there was a significant increase in blood plasma T3 with a decrease in the concentration of T4, and TTG increase during last minutes before the termination of the hypoxic load, followed by an increase in the recovery period of blood T4. In untrained individuals, at the beginning of the hypoxic state, there was an increase in the concentration of T3 with an unreliable decrease in the content of T4. Starting from 5 minutes of the study, the content of plasma T4 increased, with a simultaneous increase in the amount of TTG, and the content of T3 decreased. Conclusion: according to the results of the conducted study, there is a specific reaction on the part of thyroid hormones in response to normobaric hypoxia, aimed at economizing intracellular oxidative processes and the formation of a structural trace of adaptation. Systematic exercises with intensive physical anaerobic workouts increase the adaptive capacity of the thyroid system.